Analisis Biaya Operasional Penambangan Menggunakan Metode Full Costing pada Lubang D-12 Tambang Bawah Tanah PT. Dasrat Sarana Arang Sejati, Parambahan, Desa Batu Tanjung, Kecamatan Talawi, Kota Sawahlunto - Indri Dwi Wahyuni; Tri Gamela Saldy (Departemen Teknik Pertambangan FT UNP, 2023)
PT. Dasrat Sarana Arang Sejati is engaged in coal mining. To increase coal production, it is necessary to maximize effective working time and calculate mining operational costs. The aim of this research is to obtain coal production/month if maximizing effective working time and calculating the cost of coal production as well as profit or loss using the Full Costing method with the research object namely the PT D-12 hole. Dasrat Sarana Sejati Charcoal. The results of research and coal production calculations if maximizing effective working time is 432 tons/month, mining operational costs for January-March 2023 will be IDR. 189.432.800 cost of coal production/ton in January-March 2023 amounting to IDR 236.998/ton and profits obtained from PT's D-12 pit. Dasrat Sarana Arang Sejati for January-March 2023 amounting to Rp. 170.252200.Keywords: Coal Production, Operational Costs, Full Costing